History Teaching in the Soviet School of the 1920s-1930s: From Experiments to Nationalization and Pragmatism (on the Example of TASSR) - Shamsutdinova, Rimma Gabdarxakovna; Shuvalova, Elena Mikhailovna; Khamitov, Denis Evgenyevich (Journal of History Culture and Art Research, 2017)
This publication is devoted to the problems of history teaching in the Soviet school in the 1920s-1930s. The article presents the main conclusions and provisions that characterize the change in government policy regarding historical science in general, and the teaching of school history course, in particular. It was shown the evolution of state policy, which resulted in the fact that the government refused of the experiments of the 1920s in the 1930s. All this eventually led to the nationalization of historical science. Of all the variety of directions that existed in the late 19 - early 20th century, the government chose and turned Marxist direction into the only one that had the right to life and the right to be considered truly scientific. When writing the article, we used the system-structural approach, dialectical, general historical and logical methods, which allowed revealing the essential features of history teaching in the Soviet school. Consideration of the problem both at the all-Union level and at the regional level made it possible to identify the general and particular, the difficulties and contradictions in the adaptation of historical narrative for the purposes of teaching in the secondary school. Practical application of this publication is aimed at focusing attention of the professional community of historians and educators on the achievements of Russian historical thought, the integrated application of particular developments and recommendations developed by the Soviet historians and teachers.